The Application of The Nearest Neighbor Algorithm in Detecting Appendicitis Disease - Sari Handayani; Nelly Astuti Hasibuan; Putri Ramadhani (STMIK Budi Darma, 2018)
The expert system is a branch of artificial intelligence that facilitates the knowledge of an expert into an application that can be used to help the work of experts. The knowledge base is formed by an inference engine that translates an expert's knowledge. The result or output of the expert system can not guarantee its certainty. Therefore, it takes several methods that can be used to solve it. In this study, expert systems are applied to the medical or medical world. The following are related to the medical appendicitis disease or better known as appendicitis.Method used to improve the accuracy of the decision of the nearest neighbor algorithm. The nearest neighbor algorithm is an approach to finding a case with proximity or similarity between a new case and an old case. The results of this study is an engineering inference expertise with the aim to obtain clinical decisions of appendicitis diseases on the user (user) as medical treatment as early as